Interictal Hippocampal Spiking Influences the Occurrence of Hippocampal Sleep Spindles. Issue 12 (1st December 2015) - Frauscher, Birgit; Bernasconi, Neda; Caldairou, Benoit; von Ellenrieder, Nicolás; Bernasconi, Andrea; Gotman, Jean; Dubeau, François
Abstract: Objectives: The significance of hippocampal sleep spindles and their relation to epileptic activity is still a matter of controversy. Hippocampal spindles have been considered a physiological phenomenon, an evoked response to afferent epileptic discharges, or even the expression of an epileptic manifestation. To address this question, we investigated the presence and rate of hippocampal spindles in focal pharmacoresistant epilepsy patients undergoing scalp-intracerebral electroencephalography (EEG). Design: Sleep recording with scalp-intracerebral EEG. Setting: Tertiary referral epilepsy center. Patients: Twenty-five epilepsy patients (extratemporal: n = 6, temporal: n = 15, and multifocal including the temporal lobe: n = 4). Interventions: N/A. Measurements and Results: We analyzed associations between hippocampal spindles and hippocampal electrophysiological findings (interictal spiking, seizure onset zone) and magnetic resonance imaging volumetry. Sixteen of 25 patients (64%) had hippocampal spindles (extratemporal epilepsy: 6/6; temporal epilepsy: 10/15; and multifocal epilepsy: 0/4; P = 0.005). Median spindle rate was 0.6 (range, 0.1–8.6)/min in nonrapid eye movement sleep. Highest spindle rates were found in hippocampi of patients with extratemporal epilepsy (P < 0.001). A negative association was found between hippocampal spiking activity and spindle rate (P = 0.003). We found no association between the presence (n = 21) or absence (n = 17) of hippocampal seizure onset zone and hippocampal spindle rate (P = 0.114), and between a normal (n = 30) or atrophic (n = 8) hippocampus and hippocampal spindle rate (P = 0.195). Conclusions: Hippocampal spindles represent a physiological phenomenon, with an expression that is diminished in epilepsy affecting the temporal lobe. Hippocampal spiking lowered the rate of hippocampal spindles, suggesting that epileptic discharges may at least in part be a transformation of these physiological events, similar to the hypothesis considering generalized spike-and-waves a transformation of frontal spindles.